Evaluation of serum adiponectin and leptin levels in type 2 diabetic patients: The potential role in predicting metabolic syndrome - Sharabeh Hezarkhani; Khosro Ghojoghi; Sara Hosseinzadeh; Naser Behnampour; Farshid Fathabadi; Zahra Hesari; Hamid Reza Joshaghani (Medical Laboratory Journal)
Background: Leptin and adiponectin, two members of the adipokine family, play roles in increasing lipid metabolism and inhibiting lipogenesis. Reduced levels of these cytokines are associated with obesity and insulin resistance. This study aimed to determine the serum levels of leptin and adiponectin in type-2 diabetic patients with and without metabolic syndrome compared to a control group. Methods: Three groups of individuals participated in this study: 47 type-2 diabetic patients with metabolic syndrome (DM+MetS), 25 type-2 diabetic patients without metabolic syndrome (DM-MetS), and 40 individuals with no history of diabetes or metabolic syndrome (Control group). Fasting blood samples were collected, and serum levels of fasting blood sugar, cholesterol, triglycerides, HDL-cholesterol, and LDL-cholesterol were measured using the enzymatic method. Blood pressure, height, and weight were recorded using stadiometers, while leptin and adiponectin levels were determined via enzyme-linked immunosorbent assay. Results: A significant difference was observed between the DM+MetS group and the DM-MetS group in serum leptin (p = 0.004) and adiponectin (p < 0.001) levels. In patients with type-2 diabetes and metabolic syndrome, serum leptin (p = 0.530) and adiponectin (p < 0.001) levels were lower compared to the control group. Conclusion: A decrease in the serum levels of key adipokines, such as leptin and adiponectin, in type-2 diabetic patients may serve as a predictor of metabolic syndrome.